Prevalence and zoonotic potential of avian chlamydia in Croatia Pojavnost i zoonotski potencijal klamidija ptica u Hrvatskoj - Horvatek Tomić, Danijela; Gottstein, Željko; Lukač, Maja; Pem-Novosel, Iva; Prukner-Radovčić, Estella (2020)
Background: Zoonotic Chlamydia (C.) psittaci, can be found in different bird species, but also in other animals and humans. Recently, new species have been described, as C. gallinacea and C. avium, changing the perspective of a single causative agent of avian chlamydiosis. Genotypes of C. psittaci differ, according to their pathogenicity, and the ones isolated from parrots, turkeys and ducks are particularly pathogenic to bird breeders or owners, veterinarians, poultry farms and slaughterhouse workers. Infections in humans may pass unapparent or to the onset of systemic lung inflammation. Asymptomatic infection is most commonly found in birds, but acute systemic or chronic infections are also possible. Material and Methods: Presence of C. psittaci in birds in Croatia must be reported by law, and all registered flocks of pigeons, parrots and other birds must be examined once, and pet shops at least twice a year. In the period from 2008 to 2017, a total of 3283 avian samples were examined by real-time PCR and the presence of Chlamydiaceae, C. psittaci and C. gallinacea were detected in faecal samples or swabs. Results and Conclusions: In total, 12% of the samples were found positive for Chlamydiaceae. From the 2015, the presence of C. psittaci has also routinely been determined, whereas 34.01% positive avian samples proved to be C. psittaci. Findings of chlamydia in various avian species indicates the importance of proper implementation of the protective measures, by taking into account the zoonotic potential of chlamydia originating from birds and poultry.
Uvod: Bakteriju C. psittaci moguće je pronaći kod različitih vrsta ptica, ali i kod drugih životinja i ljudi. Nedavno su opisane nove vrste, C. gallinacea i C. avium, čijim se nalazom mijenja slika jednog od uzročnika klamidioze u ptica. Genotipovi C. psittaci razlikuju se prema svojoj patogenosti, a oni izdvojeni iz papiga, purana i pataka posebno su patogeni za uzgajivače ili vlasnike ptica, veterinare, radnike na peradarskim farmama i u klaonicama. Infekcije kod ljudi mogu proći inaparentno ili uz teške kliničke znakove upale pluća. Asimptomatska infekcija se najčešće javlja kod ptica, no moguće su i akutne sistemske ili kronične infekcije. Materijali i metode: Prisutnost C. psittaci kod ptica u Hrvatskoj mora se prijaviti prema zakonu, a sva registrirana jata golubova, papiga i drugih ptica moraju se pregledati jednom, a trgovine za kućne ljubimce najmanje dva puta godišnje. U razdoblju od 2008. do 2017. godine ukupno je pregledano 3283 uzoraka ptica primjenom metode PCR-a u stvarnom vremenu, a prisutnost Chlamydiaceae, C. psittaci i C. gallinacea dokazana je u uzorcima izmeta ili obriscima organa. Rezultati i rasprava: Ukupno je 12% uzoraka bilo pozitivno na Chlamydiaceae. Od 2015. godine, prisutnost C. psittaci također je rutinski određena te se 34.01% pozitivnih uzoraka identificiralo kao C. psittaci. Nalazi klamidije kod različitih ptičjih vrsta ukazuju na važnost pravilne provedbe zaštitnih mjera, uzimajući u obzir zoonotski potencijal klamidije koja potječe od ptica i peradi.
Bibliografija: 38 jed.
Abstract ; Sažetak.
Keywords: Chlamydia sp. -- Ptice -- Zoonoze; Hrvatska